Assessment of bidirectional relationships between circulating cytokines and periodontitis: Insights from a mendelian randomization analysis - Huang, Shi-Jia; Li, Rong; Xu, Shuo; Liu, Yuan; Li, Sheng-Hui; Duan, Sheng-Zhong (Frontiers in Genetics, 2023)
Background: The purpose of this Mendelian randomization (MR) study was to assess the causal relationship between circulating cytokines and periodontitis. Materials and Methods: We applied bidirectional two sample MR based on summary statistics of the largest publicly available genome-wide association study (GWAS). MR analyses were conducted using Inverse variance weighted (IVW), MR-Egger, Weighted median, Maximum likelihood (ML) and Robust Adjusted Profile Score (RAPS), and results obtained from IVW served as the primary outcome. Cochran Q test was used to test the heterogeneity. Pleiotropy analysis was applied using MR-Egger intercept test and MR pleiotropy residual sum and outlier (MR-PRESSO) test. Leave-one-out sensitivity and funnel plots were used for sensitivity analysis. Results: The IVW method indicated that interleukin 9 (IL9) had a positive causal relationship with periodontitis [odds ratio (OR)=1.199, 95% confidence interval (CI)=1.049-1.372, P=0.008], and interleukin 17 (IL17) had a negative causal relationship with periodontitis (OR=0.847, 95% CI=0.735-0.976, P=0.022). In bidirectional MR, periodontitis was not causally related to any of the cytokines in our study. Conclusions: Our findings provided evidence in support of potential causal associations between circulating IL9/IL17 and periodontitis.